2018
DOI: 10.4103/jgid.jgid_19_17
|View full text |Cite
|
Sign up to set email alerts
|

Head Lice among Governmental Primary School Students in Southern Jordan: Prevalence and Risk Factors

Abstract: Background:Head lice, a common social and health problem among all age groups, is especially widespread among school-aged children.Aims:This study aimed to assess the prevalence of pediculosis capitis among governmental primary school students in Southern Jordan and its related risk factors.Settings and Design:A sample of 500 primary schools students aged 6–12 from two male and two female public primary schools in four educational directorates were selected randomly in this cross-sectional study.Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
3
8
3
Order By: Relevance
“…The results of this study is not much different from the research conducted by Karimah et al (2016) in elementary school children in Jatinangor by 55.3% [10]. But Different to the results of research in elementary school children in South Jordan by Khamaiseh (2018) was 20.4% [11]. In another study by Assaedi et al (2018) showed that the infestation was 64.2% [12].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The results of this study is not much different from the research conducted by Karimah et al (2016) in elementary school children in Jatinangor by 55.3% [10]. But Different to the results of research in elementary school children in South Jordan by Khamaiseh (2018) was 20.4% [11]. In another study by Assaedi et al (2018) showed that the infestation was 64.2% [12].…”
Section: Discussioncontrasting
confidence: 93%
“…In this study, there was significant association between age and pediculosis capitis (p<0.001). Khamaiseh (2018) also found a significant association between age and pediculosis capitis with p value = 0.046 [11]. So was the study of Tohit et al (2017) with p value = 0.001 [16].…”
Section: Discussionmentioning
confidence: 98%
“…These results are in line of those reported from some areas of sub-Saharan Africa, particularly Nigeria ( Ebomoyi, 1988 , Ebomoyi, 1994 ; Okoh and Alikor, 2013 ; Salehi et al, 2014 ). However, highest prevalences have been reported in Africa ( Morsy et al, 2001 ; Sangaré et al, 2015 ) and other parts of the world ( Khamaiseh, 2018 ; Lye et al, 2017 ; Nejati et al, 2018 ; Shirvani et al, 2013 ). This variation in infestation rate between localities might be explained by many efforts, such as lice control policy, eradication strategies, number of head-to-head contacts, personal hygiene, promiscuity, socio-economic status ( Rassami and Soonwera, 2012 ; Salehi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Southern Jordan [24], the prevalence of lice infestation was 20.4 % in similar population (481 school students aged 6-12 years). The major risk factors were female gender (50.5 %), Universidad de Manizales -Facultad de Ciencias de la Salud low socioeconomic status, inadequate hygiene practices and sharing personal articles.…”
Section: Discussionmentioning
confidence: 94%